Modern Approaches to Educational Process Organization: Integration of Dual Education and Innovative Technologies (MMIT Proceedings, 2025)
This article examines contemporary trends in the development of higher education in the context of digital transformation and evolving labor market demands, analyzing the effectiveness of integrating the dual education system with innovative pedagogical technologies. It explores the mechanisms of tripartite partnership between higher education institutions, manufacturing organizations, and students, and presents the results of implementing modern digital solutions into the educational process and their impact on the quality of graduate training.